Nutrition Education As An Effort To Increase Immunity During The Covid-19 Pandemic - Diah Hermayanti; Alifia Salsabila Teka (Universitas Muhammadiyah Malang, 2022)
Background:The Covid-19 pandemic in Indonesia is starting to increase again with the emergence of the omicron variant SARS-Cov2. Efforts are needed to increase immunity, one of which is by providing nutrition education to the community. Purpose: Increase nutrition knowledge to improve immunity.Methods: This was a cross-sectional descriptive study amongAisyiyahmembers of the Bumiayu branch. Education about nutritional knowledge is given, and pre-test and post-test are also performed using a questionnaire.The total score was analyzed using paired t-test. Results: The mean value of nutritional knowledge was initially 67.37 and increased to 78.95 after receiving education. The change in knowledge was statistically significant (p = 0.002). Conclusion: The education provided has been shown to positively impact nutritional knowledge and increase immunity.